2000
DOI: 10.1159/000008757
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Prostaglandin E<sub>1</sub> Incorporated in Lipid Microspheres on Liver Injury and Regeneration after 90% Partial Hepatectomy in Rats

Abstract: The aim of this study was to assess how the administration of prostaglandin E1 incorporated in lipid microspheres (Lipo PGE1) affects liver injury and regeneration after massive hepatectomy in rats. Two hundred and eight male Wistar rats underwent 90% partial hepatectomy. Lipo PGE1 of 1, 10 or 30 μg/kg were administered intraperitoneally at 6 h prior to and 0 and 6 h after hepatectomy. Postoperative increases in serum GOT, total bilirubin, IL-6 and plasma endotoxin levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous data showed that maximal expression of COX-2 occurs 16 h after PH, causing an increase in serum levels of PGE 2 [16,38]. Both pharmacological inhibition of COX-2 and gene inactivation in COX-2 KO mice result in impaired liver regeneration, whereas supply of PGs favors the regeneration process [39]. In this study, we have used a pharmacological approach, in view of the systemic defects associated with the COX-2 null phenotype that could interfere with the regeneration process [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data showed that maximal expression of COX-2 occurs 16 h after PH, causing an increase in serum levels of PGE 2 [16,38]. Both pharmacological inhibition of COX-2 and gene inactivation in COX-2 KO mice result in impaired liver regeneration, whereas supply of PGs favors the regeneration process [39]. In this study, we have used a pharmacological approach, in view of the systemic defects associated with the COX-2 null phenotype that could interfere with the regeneration process [37].…”
Section: Discussionmentioning
confidence: 99%
“…Ninety percent hepatectomy in rats was introduced into experimental surgery as a model of fulminant hepatic failure [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] showing a high lethality. Kubota et al [30] pioneered a surgical technique that allowed a 100% survival rate after 90% PH in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The intraportal infusion of PGE1 prevents the accumulation of excessive ascites and hyperbilirubinemia in patients with small-for-size graft (15). Moreover, it has been demonstrated that pretreatment of rats with PGE1 could improve the survival rate after massive hepatectomy by inhibiting apoptosis and stimulating hepatocyte proliferation as well as heat shock protein 70 (HSP70) accumulation (16)(17)(18)(19). However, the underlying molecular mechanisms by which PGE1 exerts its protective effects on rats after massive hepatectomy are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%